The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1534/genetics.107.085795
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Analysis of the Role of Peroxisomes in the Utilization of Acetate and Fatty Acids in Aspergillus nidulans

Abstract: Peroxisomes are organelles containing a diverse array of enzymes. In fungi they are important for carbon source utilization, pathogenesis, development, and secondary metabolism. We have studied Aspergillus nidulans peroxin (pex) mutants isolated by virtue of their inability to grow on butyrate or by the inactivation of specific pex genes. While all pex mutants are able to form colonies, those unable to import PTS1 proteins are partially defective in asexual and sexual development. The pex mutants are able to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
141
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(156 citation statements)
references
References 89 publications
15
141
0
Order By: Relevance
“…Indeed, as described below, deletion analysis revealed that loss of HAD1 in C. neoformans caused phenotypes comparable to those from the loss of HAD1 in U. maydis. We also targeted the HAD1-encoded 3-OH-acyl-CoA dehydrogenase step in the mitochondrial ␤-oxidation pathway because loss of this enzyme caused the accumulation of inhibitory intermediates in A. nidulans (26,44,45). We reasoned that this might also reduce virulence for C. neoformans and therefore provide an additional incentive to target fungal ␤-oxidation as an antifungal strategy.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Indeed, as described below, deletion analysis revealed that loss of HAD1 in C. neoformans caused phenotypes comparable to those from the loss of HAD1 in U. maydis. We also targeted the HAD1-encoded 3-OH-acyl-CoA dehydrogenase step in the mitochondrial ␤-oxidation pathway because loss of this enzyme caused the accumulation of inhibitory intermediates in A. nidulans (26,44,45). We reasoned that this might also reduce virulence for C. neoformans and therefore provide an additional incentive to target fungal ␤-oxidation as an antifungal strategy.…”
Section: Resultsmentioning
confidence: 99%
“…To test the possibility that defects in ␤-oxidation caused accumulation of toxic intermediates as seen in other fungi, the wildtype strain and the mutants were grown on the alternative carbon sources galactose, lactose, and acetate (16,26,40,44,45,48). No growth was observed on lactose, and galactose generally behaved like glucose as a catabolite-repressing carbon source (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For interpretation of the references to color in this figure legend, the reader is referred to the web version of this article to be a microbody protein in A. nidulans (Valenciano et al 1998). Recently, it was shown that import of A. nidulans ICL1 in microbodies depends on the PTS2 receptor Pex7p (Hynes et al 2008). In all filamentous ascomycetes, including P. chrysogenum, ICL1 lacks a recognizable PTS, while in some yeast species and certain basidiomycetes, the protein contains a PTS1 (for alignment, see Supplementary Fig.…”
Section: In Silico Identification Of P Chrysogenum Proteins With Putmentioning
confidence: 99%